Crystal structure of (E)-(3-(4-phenoxyphenyl)acryloyl)ferrocene, C25H20FeO2 - Gao Jie; Zhang Shuang; Wang Yanan; Guo Yucong; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures)
C25H20FeO2, monoclinic, P21/c (no. 14), a = 15.9672(10) Å, b = 5.7830(4) Å, c = 20.9889(15) Å, β = 104.017(3)°, V = 1880.4(2) Å3, Z = 4, Rgt(F) = 0.0565 wRref(F2) = 0.1227, T = 173 K.